Nursing of subgingival ultrasound combined with subgingival sandblasting in the treatment of chronic periodontal disease (龈下超声联合龈下喷砂术治疗慢性牙周炎的护理体会) - DAI Xue'e (戴雪娥); WENG Haiyan (翁海燕) (Association of Integrative Nursing, 2023)
This article introduces the nursing of subgingival ultrasound combined with subgingival sandblasting technology in the treatment of chronic periodontal disease. Totally patients with chronic periodontal disease were taken as the research objects. During the clinical treatment, perioperative nursing measures such as preoperative preparation, intraoperative cooperation and postoperative rehabilitation health guidance were carried out. High-quality nursing services and comprehensive health education can help the successful completion of surgery and promote the control of periodontal disease. (本文总结龈下超声联合龈下喷砂技术治疗慢性牙周炎的护理经验。患者就诊后完善术前准备, 做好心理辅导, 提高配合度; 术中积极配合医生完成操作, 并安抚患者情绪, 确保治疗顺利; 术后加强健康宣教, 促进患者早期控制牙周炎。)